The Multicultural Liaison Officers’ Perspective in Assessing Refugee Children in the Schools - Beglari, Afarin; Thai, Huong (Refuge: Canada’s Journal on Refugees, 2000)
Any assessment, psychological, educational or speech and language, even in the native language, may pose many challenges for refugee children and their families in the schools. The Multicultural Liaison Officers are based at the schools to help families in dealing with a new educational systern. One of the areas the MLOs play a major role is in assisting the schools in assessing students. This article examines the involvement of the Multicultural Liaison Oficers and their perspectives on assessing refugee children with disabilities as well as some of the obstacles and possibilities the families and the professionals face in dealing with this process.